Plasma Complement 3 and Complement 4 Are Promising Biomarkers for Distinguishing NMOSD From MOGAD and Are Associated With the Blood-Brain-Barrier Disruption in NMOSD - Lin, Liuyu; Wu, Yuqing; Hang, Hailun; Lu, Jie; Ding, Yuanliang (Frontiers in Immunology, 2022)
ABSTRACT: Background and objective: Neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody (MOG-IgG) associated disease (MOGAD) are autoimmune inflammatory demyelinating diseases of the central nervous system (CNS). As the clinical features of NMOSD are similar to MOGAD, diagnostic confusion exists between the two diseases. To better discriminate NMOSD from MOGAD, we investigated whether the plasma levels of complement 3 (C3) and complement 4 (C4) are different in NMOSD and MOGAD during the acute attacks of the diseases. We sought to determine whether C3 or C4 has an influence on the features of NMOSD. Methods: In this observational study, data from 73 aquaporin-4 antibodies (AQP4-IgG) positive NMOSD patients and 22 MOG-IgG positive MOGAD patients were collected retrospectively. Demographics, clinical characteristics, plasma parameters, and cerebrospinal fluid (CSF) findings will be analyzed for comparability between the two groups. Immunoglobulin-G (IgG) and albumin were measured in both plasma and CSF. Plasma levels of C3 and C4 were measured and compared between the NMOSD, MOGAD, and 42 healthy controls (HC). The correlations between plasma C3, C4, and NMOSD clinical parameters were analyzed.